2021
DOI: 10.1136/bmjopen-2020-042196
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and functional impairments in children with attention deficit hyperactivity disorder in China: a hospital-based retrospective cross-sectional study

Abstract: ObjectivesThe aim of this study was to assess comorbidity patterns and functional impairment in children with and without attention deficit hyperactivity disorder (ADHD).DesignHospital-based retrospective cross-sectional study; data collection occurred between 2016 and 2019.Settings and patientsA total of 8256 children and adolescents, 6–17 years of age, with suspected ADHD agreed to participate in this hospital-based cross-sectional study over a 4-year period in China. Comorbidities and social functions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This developmental neurobiological disorder reduces specific brain functions related to planning, initiating, and completing tasks and assignments (Barkley, 2022; Posner et al, 2020), as genomic data have confirmed (Faraone & Larsson, 2019; Grimm et al, 2020). Furthermore, approximately 50%–70% of those diagnosed with ADHD have one or more comorbidities, such as anxiety, depression, or behavioral problems (Mitchison & Njardvik, 2019; Mohammadi et al, 2021; Shi et al, 2021), which untreated can aggravate other hyperactivity symptoms (Barkley, 2022). Due to the multifaceted and often complex nature of ADHD, ongoing research on appropriate collaborative family support is needed (Babinski & Sibley, 2022; Gisladottir & Svavarsdottir, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This developmental neurobiological disorder reduces specific brain functions related to planning, initiating, and completing tasks and assignments (Barkley, 2022; Posner et al, 2020), as genomic data have confirmed (Faraone & Larsson, 2019; Grimm et al, 2020). Furthermore, approximately 50%–70% of those diagnosed with ADHD have one or more comorbidities, such as anxiety, depression, or behavioral problems (Mitchison & Njardvik, 2019; Mohammadi et al, 2021; Shi et al, 2021), which untreated can aggravate other hyperactivity symptoms (Barkley, 2022). Due to the multifaceted and often complex nature of ADHD, ongoing research on appropriate collaborative family support is needed (Babinski & Sibley, 2022; Gisladottir & Svavarsdottir, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Attention deficit hyperactivity disorder (ADHD), also known as hyperactivity disorder, is a childhood-onset neurodevelopmental disorder characterized by stunted growth and inattention, hyperactivity of movement, and impaired impulsivity (Thapar & Cooper, 2016). Recent studies have shown that the global prevalence of ADHD ranges from 1.4% to 3.0% (Thapar & Cooper, 2016), is more common in boys than girls, and is as high as 5.7% to 6.5% in China (Liu et al, 2018; X. Shi et al, 2021; Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…6 About 40%-80% of children and 80% of adults experience at least one comorbid psychiatric disorder such as anxiety, mood disorders and substance use disorders. [7][8][9][10] Those diagnosed with ADHD also have a higher risk of school failure, antisocial behaviour, accidental injuries, and premature death including attempted and completed suicide. 11 Given the significant impairments of ADHD on academic, social, occupational, and mental functions, it is imperative to conduct surveillance of the prevalence and incidence trends of ADHD over time for planning healthcare services and resource allocation.…”
Section: Introductionmentioning
confidence: 99%
“…6 About 40%–80% of children and 80% of adults experience at least one comorbid psychiatric disorder such as anxiety, mood disorders and substance use disorders. 710 Those diagnosed with ADHD also have a higher risk of school failure, antisocial behaviour, accidental injuries, and premature death including attempted and completed suicide. 11…”
Section: Introductionmentioning
confidence: 99%